TANTANGAN DAN STRATEGI DALAM MANAJEMEN RISIKO INVESTASI CRYPTOCURRENCY DI INDONESIA - Muhammad Zaki Zikrillah Baharuddin Nasution; Abdul Hakim; Andra Maulana (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Promotion is an activity carried out to convey, disseminate, and offer products, so that potential consumers are interested in buying. In the implementation of the promotion, CV. Pentaland Jaya abadi uses website media and brochures that still contain 2-dimensional images and information about housing so that potential consumers are less interested because consumers cannot see the exterior and interior shapes directly. Potential consumers usually get brochures through project locations that are still under construction, after that contact the marketing department. One way to solve this problem can be to use augmented reality technology with the appropriate development method is the Multimedia Development Life Cycle (MDLC) which includes Concept, Design, Material Collecting, Assembly, Testing, and Distribution so that this research can produce an android-based augmented reality application that can display 3 dimensional virtual shapes from 3 housing estates including calista haus, grand ayahanda residence and calista homey. From each housing produces 3 dimensional objects on the exterior and interior so that it can provide interest in buying house objects and in addition to that it also helps in the marketing department in promoting housing objects without the need to show many miniatures that require time and also large places.Â Keywords: Cryptocurrency, Investment, Risk Management, Market Exchange. Abstrak: Cryptocurrency telah menjadi instrumen investasi yang signifikan di Indonesia, mencerminkan transformasi digital dalam lanskap keuangan kontemporer. Penelitian ini menganalisis kompleksitas investasi cryptocurrency, dengan fokus pada karakteristik pasar, dinamika regulasi, dan strategi manajemen risiko yang diperlukan dalam konteks ekonomi Indonesia. Menggunakan pendekatan kualitatif deskriptif, studi ini menyelidiki perkembangan cryptocurrency dari perspektif teknologi, investor, dan kerangka hukum. Temuan penelitian mengungkapkan pertumbuhan yang mengesankan, dengan jumlah investor cryptocurrency mencapai 21,3 juta pada tahun 2024, didominasi oleh generasi muda. Badan Pengawas Perdagangan Berjangka Komoditi (Bappebti) telah mengakui 32 market exchange resmi dan 545 aset kripto yang dapat diperdagangkan. Penelitian mengidentifikasi volatilitas harga sebagai tantangan utama, dengan fluktuasi yang dapat mencapai ratusan persen dalam periode singkat. Strategi mitigasi risiko yang direkomendasikan mencakup diversifikasi portofolio cryptocurrency dan strategi hedging dengan aset tradisional. Studi menekankan pentingnya pemahaman mendalam tentang teknologi blockchain, regulasi yang berkembang, dan dinamika pasar cryptocurrency. Kesimpulan penelitian menyoroti bahwa keberhasilan investasi cryptocurrency membutuhkan pendekatan strategis, edukasi berkelanjutan, dan manajemen risiko yang komprehensif.Â Kata kunci: Cryptocurrency, Investasi, Manajemen Risiko, Market Exchange.